Integrated Analysis of the Anoikis‐Related Signature Identifies Rac Family Small GTPase 3 as a Novel Tumor‐Promoter Gene in Hepatocellular Carcinoma - Dong Wu; Ze‐Kun Liu; Ying Sun; Chu‐Heng Gou; Run‐Ze Shang; Meng Lu; Ren‐Yu Zhang; Hao‐Lin Wei; Can Li; Ying Shi; Cong Zhang; Yu‐Tong Wang; et al. (MedComm)
ABSTRACT Anoikis resistance in hepatocellular carcinoma (HCC) cells boosts survival and metastasis. This study aimed to establish an anoikis‐related genes (ARGs)‐based model for predicting HCC patients’ outcomes and investigate the clinicopathological significance and function of crucial ARGs. The transcriptional expression patterns for HCC cohorts were compiled from TCGA, GEO and ICGC. Univariate and LASSO multivariate analyses were performed to screen for prognostic ARGs. Gain‐ and loss‐of‐function studies, RNA sequencing, and mass spectrometry were employed to elucidate the underlying mechanisms of ARGs in HCC. We established a five‐gene ARGs risk model for HCC prognosis, with an AUC value of 0.812 for 1‐year survival. Among the five genes, Rac family small GTPase 3 (RAC3) was upregulated in HCC relative to adjacent normal tissues and negatively correlated to overall survival and disease‐free survival of patients with HCC. Silence of RAC3 in HCC cells resulted in an increased cell apoptosis and diminished cell proliferation and invasion. Mechanistically, we uncovered that RAC3 binding with SOX6 propelled the advancement of HCC cells through NNMT‐mediated stimulation of the cAMP/MAPK/Rap1 signaling. In particular, EHop‐016, a small molecule inhibitor targeting RAC3, significantly suppressed HCC progression.